Case Notes: South Africa's Policy Incoherence: An Update on the Knysna Wi-Fi Project - Esselaar, Steve; Soete, Pieter (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2007)
In the past, the main obstacle against building network infrastructure was the cost. Technological advances, however, have meant that building a functional, low-cost network is possible. Knysna is the first municipality in South Africa to achieve this. The problem is not the infrastructure but the connection to the larger networks of the mobile and fixed-line operators. The incumbents’ incentives are to prevent interconnection (or at least to delay it) on the basis of maintaining their dominance. In the telecommunications sector in South Africa, the only way to overcome this problem is via regulation. Yet regulation has to balance two sometimes competing interests – investment in infrastructure and competition. The Knysna Uni-Fi project has operated outside of any enabling regulation for competition and investment and this has negatively impacted upon its commercial success. Any regulatory intervention imposed upon the market has to balance the interests of competition and investment. In the South African market, given the huge dominance by the incumbents, that balance must change to favour new entrants. Until this takes place Knysna is not a replicable model for South Africa.